Gastrointestinal Tract Malrotation: Etiology and Risk Factors - Annisa Yumna Nabiilah; Dewa Ayu Vania; I Komang Gede Andhika Wibisana; Rizqina Alya Shafa; Sicilia Putri Atari; Zikrul Haikal (Jurnal Biologi Tropis, 2023)
Malrotation is a congenital abnormal position of the intestine within the peritoneal cavity and usually involves the small intestine and large intestine. Intestinal malrotation occurs at a rate of 1 in 500 live births. Male predominance was present in neonates with a male-to-female ratio of 2:1. Up to 40% of patients with malrotation present within the first week of life, 50% up to one month of age and 75% by one year of age. Purpose: To determine the etiology and risk factors for gastrointestinal tract malrotation. Conclusion: Malrotation is a congenital abnormal position of the intestine within the peritoneal cavity and usually involves the small intestine and large intestine. Gastrointestinal (GI) malrotation, sometimes referred to as incomplete rotation or non- rotation of the bowel, is any deviation from the physiological rotation and/or fixation of the GI tract during embryonic development. During the development of the GI tract, the 3 parts of the tract, namely the foregut, middle, and hindgut, usually protrude from the abdominal cavity and undergo a counterclockwise rotation of 270 degrees. Basically, rotational and fixation anomalies are caused by failure of various embryological stages. Clinical manifestations are divided into 4, namely Midgu Volvulus, Intestinal Obstruction, Gasroschisis, and Omphalocele. The main management of intestinal malrotation is a surgical procedure. Other therapies are given to stabilize the patient and are supportive.